2021
DOI: 10.1093/europace/euab162
|View full text |Cite
|
Sign up to set email alerts
|

Comparing clinical performance of current implantable cardioverter-defibrillator implantation recommendations in arrhythmogenic right ventricular cardiomyopathy

Abstract: Aims Arrhythmogenic right ventricular cardiomyopathy (ARVC) patients have an increased risk of ventricular arrhythmias (VA). Four implantable cardioverter-defibrillator (ICD) recommendation algorithms are available The International Task Force Consensus (‘ITFC’), an ITFC modification by Orgeron et al. (‘mITFC’), the AHA/HRS/ACC guideline for VA management (‘AHA’), and the HRS expert consensus statement (‘HRS’). This study aims to validate and compare the performance of these algorithms in ARV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“… 4 , 16 Severe RV dysfunction is also one of the Class I indications for an ICD in patients with ARVC in accordance with four stratification algorithms. 17 In this study, it has also been shown that RV dysfunction is also an independent predictor of VT resulting in ATP.…”
Section: Discussionsupporting
confidence: 58%
“… 4 , 16 Severe RV dysfunction is also one of the Class I indications for an ICD in patients with ARVC in accordance with four stratification algorithms. 17 In this study, it has also been shown that RV dysfunction is also an independent predictor of VT resulting in ATP.…”
Section: Discussionsupporting
confidence: 58%
“…Indications for ICD are based on the ARVC disease criteria 105 and specific risk factors for VA (Table 1). 154 The course is usually dominated by VA, as symptomatic HF developed in only 13% of index cases in this large series, with only 4% going to heart transplantation.…”
Section: Phenotypes Of Genetic Cardiomyopathymentioning
confidence: 70%
“…Recently, the comparison of the clinical performance of current algorithms for ICD implantation in ARVC confirmed that both the 2015 ITFC and the modified ITFC recommendations provide the highest ICD protection rates. 114 , 115 The 2015 ITFC remain the best performing algorithm to indicate an ICD in ARVC, if one considers a threshold of >6% 5-year risk (similar to the threshold for HCM patients) of fast VT. 115 …”
Section: Implantable Cardioverter Defibrillator Therapymentioning
confidence: 99%